Design of Mobile Tracking Application System for Postgraduate Office at UUM - Ali Hmedat, Nooreddin Mansoor (2009)
Mobile devices technology developed rapidly, most of students have mobile devices and they use the communication technologies devices to accomplish their tasks. Students face problems to track their application forms status since they have to call or go to the postgraduate office to check about their application forms status, this study led to the development of Mobile web-based prototype to help the students to submit their application forms from their mobiles and track their application forms by using the mobile application tracking system which reduces the efforts. Postgraduate office can view and change the status of application forms directly by using web tracking system which has been developed. Two systems prototype has been developed and tested successfully. The future work is how to implement those systems online web world and make some enhancement to meet the requirements of technologies.